Comparison of familiarity and competency in using online assessment platforms among lecturers before and during movement control order period - Khaing, Aye Thi; Mohamed Bakrim, Norbaiyah; Ismawi, Hidayatul Radziah; Abd Rahim, Nour El Huda; Wahid, Hanan Hamimi; Ismail, Soraya; Mohd Radzuan, Hazulin; Mat Harun, Noraihan; Mohd Noor, Mohd Fadly; Abdul Rahim, Roslina; Mohd Zainudin, Maizura; Hamzah, Hairul Aini; et al. (2020)
INTRODUCTION: The COVID-19 pandemic affected all academic activities nationwide including at International Islamic University Malaysia (IIUM). The Basic Medical Sciences (BMS) department, Faculty of Medicine needed to adopt the Emergency Remote Teaching and Learning (ERTL) imposed by the university since traditional classroom teaching was no longer an option. Online platforms such as Google Forms, Kahoot, Microsoft Teams have been used as alternatives to the conventional method of assessment for the past few years. In IIUM, a learning management system known as iTa’leEM (Innovative teaching and learning environment system), established since 2013 has become the main online platform for teaching as well as assessment. OBJECTIVE: This research aimed to compare the familiarity and competency in using iTa’leEM as an online assessment platform among lecturers before the commencement of Movement Control Order (MCO) versus after the completion of the first online Integrated Assessment (IA) session in July 2020. The survey was conducted in the recently developed BMS exam unit involving 14 lecturers. The respondents completed the same set of questionnaires at the beginning of ERTL period and after the first online IA session. RESULTS: Before MCO, 14% of lecturers utilized iTa’leEM as well as other online assessment tools whereas the percentage inclined to 86% and 78% in using iTa’leEM and other online assessment platforms respectively after first online IA. 71% of respondents agreed that they were not familiar and 79% were not competent in using iTa’leEM before MCO. The percentage reduced to 7% who remained not familiar and competent after the first online IA. Only 7% of respondents agreed they received proper training regarding online assessment platform before MCO as compared to 64.3% after the first online IA. DISCUSSION: Despite online assessment platforms have been available for many years, they have been less utilized by the lecturers prior to MCO. This might due to the lack of proper training and lecturers preferred the conventional face-to-face sessions which were more convenient. The findings suggested that ERTL period has enforced the lecturers to explore the online assessment platforms. CONCLUSION: Adequate continuous training should be emphasized to further enhance the capability of lecturers to employ the online assessment platforms effectively.